The Relationship Between Perceived Social Support and Self-Compassion in Student - Iklila Aulia, Akza; Fitriani, Yulia (Rifa'Institute, 2024)
Introduction: This study discusses the relationship between perceived social support and self-compassion in high school students aged 15-17 years and have / are participating in organizational activities at school and outside school and get support from friends, family, or significant others. Objective: This study aims to examine the relationship between self-compassion and perceived social support in high school students who have participated in organizational activities at school and outside school. Method: This study is a quantitative research using a correlational method that aims to see if there is a relationship between perceived social support and self-compassion variables. Result and Discussion: The results of this study obtained a correlation coefficient value of 0.562 which shows the strength of the correlation between self-compassion variables and perceived social support is in the strong category. The higher the perceived social support in the individual, the higher the self-compassion possessed by the individual. Conclusion: So it can be concluded that Ha is acceptable that there is a relationship between perceived social support and self-compassion